New challenges for banking, financial services and insurance - Radić Nikola (Trendovi u Poslovanju)
The crisis with the COVID-19 pandemic shows investors, policy makers and the general public that natural disasters can cause economic damage on an unprecedented scale. The pandemic has made customer experience even more differentiated, so banks, financial service providers and insurance companies need to optimize their operations and transform existing business models to meet new requirements and withstand competitive pressure. Because the processes are the "veins" of a highly regulated business, they must adapt to unprecedented change. Changing business models, disruptive technologies, and compliance pressures are forcing traditional institutions to reorganize the way they do business. Digital transformation, the macro trend that has defined the past decade, has accelerated at an incredible rate during 2020. Creative new solutions are made out of the need for people to connect despite physical distance. In addition, customer expectations have changed, so many of them want to be provided with ongoing personalized services. But moving from the old service delivery system to modern solutions has never been an easy task.